Effect of Macroeconomic Variables on Stock Market Returns in India - Ojah, Chitrajyoti (International Journal of Psychosocial Rehabilitation, 2020)
The macroeconomic variables and stock market index are inter-linked. The objective of this paper is to investigate the cointegration between BSE Sensex and Macroeconomic variables.This study uses monthly data from April 2014 to June2019 to find the inter-relationship between BSE Sensex returns and selected macroeconomic variables by applying VECM technique. The five macroeconomic variables viz. index of industrial production, wholesale price-index, exchange rate, interest rate and foreign portfolio investment have been considered to represent the indicator of the economy in India. The BSE Sensex shows a positive relationship with index of industrial production while a negative relationshipwith the interest rate in the estimation. However, in some cases, probable direction of macroeconomic variable varies.